A spatial approach to duet function in Adelaide's warbler, Setophaga adelaidae - Samantha W. Krause; Tyler R. Bonnell; Marcus J. Dostie; Samantha I. Booth; Peter C. Mower; David M. Logue (Animal Behaviour, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Skeletal muscle atrophy induced by aging and disuse atrophy are strongly associated with the upregulation of the endoplasmic stress protein CHOP in rats - J. Max Michel; Joshua S. Godwin; Nathan R. Kerr; Thomas E. Childs; Frank W. Booth; C. Brooks Mobley; David C. Hughes; Michael D. Roberts (Molecular Biology Reports, 2025)
Background While canonical anabolic and proteolytic pathways have been well examined in the context of skeletal muscle proteostasis, the roles of endoplasmic reticulum stress (ERS) and the induced unfolded protein response (UPR) are underappreciated. Thus, we aimed to determine whether aging and/or disuse atrophy in rats altered skeletal muscle ERS/UPR markers. Methods and Results Soleus (SOL) and plantaris (PLT) muscles of 3-month-old (mo), 6 mo, 12 mo, 18 mo, and 24 mo rats (9–10 per group, 48 in total) were analyzed for UPR proteins with further analysis performed on the protein CHOP. The gastrocnemius muscles of 4 mo rats that had undergone hindlimb immobilization (HLI, n = 12) or sham casting (CTL, n = 12) were analyzed for similar targets as well as more extensive CHOP-related targets. CHOP protein was greater in the PLT and SOL of 18 and 24 mo rats versus other age groups ( P < 0.05). Moreover, negative correlations existed between CHOP expression and normalized PLT ( R =-0.702, P < 0.001) and SOL ( R =-0.658, P < 0.001) muscle weights in all rats analyzed at different ages. CHOP protein expression was also greater in the gastrocnemius of HLI versus CTL rats ( P < 0.001), and a negative correlation existed between CHOP protein expression and normalized muscle weights in these rats ( R =-0.814, P < 0.001). Nuclear CHOP protein levels ( P < 0.010) and genes transcriptionally regulated by CHOP were also greater in HLI versus CTL rats ( P < 0.001) implicating transcriptional activity of CHOP is elevated during disuse atrophy. Conclusions CHOP is operative during aging- and disuse-induced skeletal muscle atrophy in rodents, and more research is needed to determine if CHOP is a key mechanistic driver of these processes.

Investigation of GSDME results in the identification of the first pathogenic synonymous variants and genotype-phenotype correlations - Joseph J. Chin; W. Daniel Walls; Kai Wang; Amanda M. Odell; Diana L. Kolbe; Kevin T. A. Booth; Hela Azaiez; Richard J. H. Smith (Human Genetics, 2025)
Despite advances in the genetic diagnosis of hearing loss, there remains room for improvement. One way to improve the genetic diagnostic rate is the proper assessment of synonymous variants that are often bioinformatically filtered out. We used GSDME as a model to demonstrate the importance of assessing synonymous variants. Variants in the gene GSDME (also known as DFNA5 ) are associated with autosomal dominant nonsyndromic hearing loss. The hearing loss is typically progressive and downsloping. All reported causative variants of GSDME -related hearing loss involve the skipping of exon 8, which results in the expression of a constitutively active, but truncated protein that induces apoptosis of cochlear hair cells. A retrospective search of previously tested patients identified 3 novel pathogenic synonymous GSDME variants. The functional impact of these variants was confirmed in vitro via a minigene splicing assay. We also observed variant-dependent differences in the levels of aberrant splicing, leading us to hypothesize that partial loss of splicing will result in a less severe hearing loss phenotype as compared to complete loss of splicing. Audiometric analysis found an association between complete loss of splicing and greater initial and/or more quickly progressing hearing loss as compared to partial loss of splicing. Over the course of the study, we also found limited correlation between in silico prediction and in vitro observed effects of a variant on splicing, indicating the need to cautiously apply in silico prediction tools in the context of genetic diagnosis.

Trade regulations drive improved global shark and ray management - Mark E. Bond; Hollie Booth; Akshay Tanna; Sarah L. Fowler; Carlos J. Polo-Silva; K.H. Stanley Shea; Floriane Cardiec; Elisabeth F. Mansur; Rima W. Jabado (Marine Policy, 2025)

Associations between local-scale soil and tree context factors and Acute Oak Decline (AOD): plant-soil feedbacks and the cause-effect conundrum - Liz J. Shaw; Mojgan Rabiey; Mateo San José; Toni-Kim Clarke; Alice Broome; Luci J. Corbett; Oliver R. Booth; Glyn A. Barrett; Gail M. Preston; Nadia Barsoum; Karsten Schönrogge; Robert W. Jackson; et al. (Plant and Soil, 2025)
Background and aims Acute oak decline (AOD), a decline syndrome affecting mature oaks, involves bacterial pathogens which likely act as opportunists under host stress. Trees displaying symptoms (bleeding cankers) appear in localized clusters, not whole stands. This study investigates the potential involvement of local-scale factors, in interaction with large-scale environmental drivers, in influencing onset and progression of AOD. Methods AOD-symptomatic ( n = 30) and asymptomatic trees ( n = 30) across three UK oak woodlands were assessed for tree characteristics, their surrounding context, and soil properties. Results Tree health status was linked to significant differences in soil and tree properties across sites. Symptomatic trees exhibited greater loss of crown density, lower local stand (0–20 m) basal area and shallower depth to gleying. Significant differences in soil properties included lower concentrations of Olsen P, total N, and exchangeable Mg in symptomatic trees, alongside higher exchangeable Fe, especially at 40–50 cm depth. Depth to gleying and exchangeable Fe were identified as the most influential predictors of AOD. Conclusions AOD symptomatic trees may experience seasonal soil water saturation closer to the surface compared to asymptomatic trees, resulting in a higher proportion of their roots being exposed to an anoxic, iron-reducing environment. This study is the first to report such an association between gleying depth, likely seasonal water saturation, and symptom status for AOD. It is unclear whether water balance and associated soil nutrient variations are predisposing factors or consequences of declining tree health, though the identified local-scale factors likely contribute to AOD. A feedback loop is conceptualised where declining tree health worsens soil conditions, creating a negative cycle that accelerates tree decline.

Improving conservation outcomes for seadragons: data, knowledge gaps, and future directions - Chrissy A. Tustison; Nerida G. Wilson; Greg W. Rouse; David J. Booth; Maarten De Brauwer (Reviews in Fish Biology and Fisheries, 2025)
Seadragons are charismatic fishes endemic to Australia’s Great Southern Reef and are flagships for marine biodiversity. Due to their unique appearances and behaviors, seadragons are of interest for both scientific research and broader conservation purposes. However, studies on wild seadragon populations are challenging to implement, and peer-reviewed data on population demographics, life histories, and other aspects of seadragon biology and ecology are currently limited. Seadragon habitats, including kelp-covered reefs and seagrass meadows, have declined in various areas of the southern Australian coast, spurring concerns that seadragon abundances may also be contracting. The lack of range-wide baseline data on seadragon populations has precluded a robust understanding of their vulnerability to extinction, and further conservation-focused research has been recommended by past studies. Here, we summarize existing research on the three known seadragon species: common, leafy, and ruby seadragons, with the aim of improving future conservation outcomes for seadragons. Range-wide population size estimates and trends in abundance data are key knowledge gaps preventing accurate extinction risk assessments. Lack of data about basic ecological and biological factors such as longevity and reproduction further hinder effective conservation actions. We describe developing research methodologies including citizen science, machine learning, habitat mapping, and molecular methods that show promise for improving outcomes for these iconic fishes and the habitats they rely on.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Ontogenetic change in body shape for white sharks, Carcharodon carcharias , in Australian waters - Emily Hunt; Russell W. Bradford; David J. Booth; Cameron Doak; Toby A. Patterson; Victor M. Peddemors (Journal of Fish Biology, 2025)
The analysis of how biological shape changes across ontogeny can provide us with valuable information on how species adapt behaviorally, physiologically, and ecologically. The white shark Carcharodon carcharias is one of the largest and most widely distributed apex predators globally, yet an understanding of ontogenetic changes in body shape and relative scaling of length and weight measures is limited, especially in relation to foraging ecology. Through analysis of a suite of shape‐related metrics, we identified ontogenetic patterns of scaling throughout development. Isometric growth was exhibited for most metrics, failing to show a significant deviation from an isometric slope of 1.0 for length–length relationships, and 3.0 for weight–length relationships. The most notable difference from this trend was the negative allometric growth observed for the upper caudal‐fin lobe length, trunk length, and the mouth length. The surface area of the fins also presented a strong, positive relationship with precaudal length (PCL) and the girth at the pectoral fin. Negative allometric growth was exhibited for three of the fins (pectoral, upper caudal fin, and lower caudal fin) against PCL, exhibiting a significant deviation from the expected isometric growth of 2.0 for area–length relationships. There were no significant differences in morphometric relationships between geographic regions within Australia that samples were collected from. No differences between the sexes were identified; however, this may be an artifact of the lack of mature animal samples. Conversely, life stage was found to have a significant effect on the girth–length and weight–length relationships. The development of regression equations for morphometric measures allows the assessment of white shark body condition and may serve as an assessment tool to understand the potential impacts of human‐induced environmental change on white sharks.

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Insecticide exposure can increase burrow network production and alter burrow network structure in soil dwelling insects (Agriotes spp.) - Samuel W. Booth; Benedikt Kurtz; Martine I.de Heer; Sacha J. Mooney; Craig J. Sturrock (Pedobiologia, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Habitat value of subsea wells and pipelines for fishery target species in Australia - Dianne McLean; Conrad W. Speed; Matthew Jon Birt; Jamie Colquhoun; Mark Case; Marcus Stowar; Todd Bond; Daniel Ierodiaconou; Sasha K. Whitmarsh; Michael D. Taylor; Sam Wines; David John Booth; et al. (Frontiers in Marine Science, 2022)
Subsea pipelines and wells installed to support the oil and gas industry represent some of the most extensive and numerous anthropogenic structures throughout global marine ecosystems. There remains a paucity of information on the habitat value of these structures for fishery target species and, as a result, little understanding of how decommissioning should be conducted to minimise impacts to populations of these economically and socially important species. We assess the diversity and abundance of species that are targets of recreational and commercial fisheries on 33 subsea wells and 17 pipelines across the tropical northwest and temperate southeast marine regions of Australia. We examine relationships between fish identity and abundance and a range of environmental (e.g., depth, location), infrastructure-specific (e.g., pipeline position, diameter, age, length of pipeline, height of well, position on well), and biological (% cover of epibiota) variables using video filmed by remotely operated vehicles during their routine offshore inspection and maintenance campaigns. A total of 100 fishery target species were observed across subsea well and pipeline infrastructure, 56 species uniquely observed on pipelines and nine unique to wells. The families Lutjanidae (snapper), Serranidae (rock cods, groupers, perch), and Carangidae (trevallies) were most common and abundant on both wells and pipelines. In the northwest, lutjanids were most abundant around the base of wells, in shallow depths, on shorter wells, and where pipelines spanned the seafloor. A greater number of fishery target species and abundance of ocean perch ( Helicolenus spp.) were also associated with pipelines that spanned the seafloor in temperate southeast Australia. The combined biomass of three species of snapper on wells in the northwest was 1,270 kg, with production levels for these species on each well estimated to be 105.2 g m 2 year -1 . The present study serves as an important reference point for informing decommissioning decisions for pipeline and well infrastructure and demonstrates the utility of industry-held data for science. We suggest that key predictor variables identified here be incorporated into comprehensive before-after-control-impact scientific studies for specific fields/assets to enable the prediction of potential impacts of decommissioning scenarios on marine communities present and quantification of such impacts after the decommissioning activity has occurred.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Fear at the top: killer whale predation drives white shark absence at South Africa’s largest aggregation site - AV Towner; RGA Watson; AA Kock; Y Papastamatiou; M Sturup; E Gennari; K Baker; T Booth; M Dicken; W Chivell; S Elwen; T Kaschke; et al. (African Journal of Marine Science, 2022)

The impact of varicella vaccination on paediatric herpes zoster epidemiology: a Canadian population-based retrospective cohort study - Ellen Rafferty; Laura Reifferscheid; Margaret L. Russell; Stephanie Booth; Lawrence W. Svenson; Shannon E. MacDonald (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
The impact of universal varicella vaccination on herpes zoster (HZ) risk in unvaccinated and vaccinated children, and its long-term influence on HZ epidemiology, remains unknown. We conducted a retrospective cohort study using population-based administrative health data for children born between 1993 and 2018 (n = 924,124). We calculated age-specific cumulative HZ incidence rates by vaccination status for cohorts born before (1993–1999) and after (2000–2018) programme implementation; results were used to calculate relative risk of HZ by age group, vaccination status and vaccine availability period. Annual HZ incidence rates were calculated for 1993–2018. HZ risk was higher among unvaccinated children compared to vaccinated children across age groups; 64% higher before universal vaccination (RR: 0.36, 95% CI: 0.33, 0.39), and 32% higher after universal vaccination (RR: 0.68, 95% CI: 0.64, 0.73). Among unvaccinated children, HZ risk was 60% lower after vaccine programme implementation (RR: 0.40, 95% CI: 0.38, 0.43). Two-dose receipt corresponded with a 41% lower risk of HZ compared to one-dose receipt (RR: 0.59, 95% CI: 0.53, 0.65). Crude annual HZ incidence rates declined 64% after programme implementation, with decreases observed across age groups. Universal varicella vaccination programme implementation corresponds to decreased paediatric HZ incidence across age groups, in both vaccinated and unvaccinated individuals. Results from this study can be used to help inform varicella vaccination programme decision-making in other countries.

A perturbed parameter ensemble of HadGEM3-GC3.05 coupled model projections: part 1: selecting the parameter combinations - David M. H. Sexton; Carol F. McSweeney; John W. Rostron; Kuniko Yamazaki; Ben B. B. Booth; James M. Murphy; Leighton Regayre; Jill S. Johnson; Ambarish V. Karmalkar (Climate Dynamics, 2021)

A comparative analysis of genetic hearing loss phenotypes in European/American and Japanese populations - W. Daniel Walls; Hideaki Moteki; Taylor R. Thomas; Shin-ya Nishio; Hidekane Yoshimura; Yoichiro Iwasa; Kathy L. Frees; Carla J. Nishimura; Hela Azaiez; Kevin T. Booth; Robert J. Marini; Diana L. Kolbe; et al. (Human Genetics, 2020)

Finding plausible and diverse variants of a climate model. Part II: development and validation of methodology - Ambarish V. Karmalkar; David M. H. Sexton; James M. Murphy; Ben B. B. Booth; John W. Rostron; Doug J. McNeall (Climate Dynamics, 2019)

Correction to: Overexpression of Protein Kinase Inhibitor Alpha Reverses Rat Low Voluntary Running Behavior - Kolter B. Grigsby; Gregory N. Ruegsegger; Thomas E. Childs; Frank W. Booth (Molecular Neurobiology, 2019)

Overexpression of Protein Kinase Inhibitor Alpha Reverses Rat Low Voluntary Running Behavior - Kolter B. Grigsby; Gregory N. Ruegsegger; Thomas E. Childs; Frank W. Booth (Molecular Neurobiology, 2019)

Outnumbered: a new dominant ant species with genetically diverse supercolonies in Ethiopia - D. M. Sorger; W. Booth; A. Wassie Eshete; M. Lowman; M. W. Moffett (Insectes Sociaux, 2017)

Validation of an in vitro model of erbB2+ cancer cell redirection - Jang Pyo Park; Walker M. Blanding; Jessica A. Feltracco; Brian W. Booth (In Vitro Cellular & Developmental Biology - Animal, 2015)

Cocaine-induced locomotor activity in rats selectively bred for low and high voluntary running behavior - Jacob D. Brown; Caroline L. Green; Ian M. Arthur; Frank W. Booth; Dennis K. Miller (Psychopharmacology, 2015)

Resolving issues with environmental impact assessment of marine renewable energy installations - Ilya M. D. Maclean; Richard Inger; David Benson; Cormac G. Booth; Clare B. Embling; W. James Grecian; Johanna J. Heymans; Kate E. Plummer; Michael Shackshaft; Carol E. Sparling; Ben Wilson; Lucy J. Wright; et al. (Frontiers in Marine Science, 2014)

Widespread dust deposition on North American peatlands coincident with European land-clearance - Alex W. Ireland; Michael J. Clifford; Robert K. Booth (Vegetation History and Archaeobotany, 2014)

Changing forest water yields in response to climate warming: results from long‐term experimental watershed sites across North America - Irena F. Creed; Adam T. Spargo; Julia A. Jones; Jim M. Buttle; Mary B. Adams; Fred D. Beall; Eric G. Booth; John L. Campbell; Dave Clow; Kelly Elder; Mark B. Green; Nancy B. Grimm; et al. (Global Change Biology, 2014)
Climate warming is projected to affect forest water yields but the effects are expected to vary. We investigated how forest type and age affect water yield resilience to climate warming. To answer this question, we examined the variability in historical water yields at long‐term experimental catchments across Canada and the United States over 5‐year cool and warm periods. Using the theoretical framework of the Budyko curve, we calculated the effects of climate warming on the annual partitioning of precipitation ( P ) into evapotranspiration ( ET ) and water yield. Deviation ( d ) was defined as a catchment's change in actual ET divided by P [ AET / P ; evaporative index ( EI )] coincident with a shift from a cool to a warm period – a positive d indicates an upward shift in EI and smaller than expected water yields, and a negative d indicates a downward shift in EI and larger than expected water yields. Elasticity was defined as the ratio of interannual variation in potential ET divided by P ( PET / P ; dryness index) to interannual variation in the EI – high elasticity indicates low d despite large range in drying index (i.e., resilient water yields), low elasticity indicates high d despite small range in drying index (i.e., nonresilient water yields). Although the data needed to fully evaluate ecosystems based on these metrics are limited, we were able to identify some characteristics of response among forest types. Alpine sites showed the greatest sensitivity to climate warming with any warming leading to increased water yields. Conifer forests included catchments with lowest elasticity and stable to larger water yields. Deciduous forests included catchments with intermediate elasticity and stable to smaller water yields. Mixed coniferous/deciduous forests included catchments with highest elasticity and stable water yields. Forest type appeared to influence the resilience of catchment water yields to climate warming, with conifer and deciduous catchments more susceptible to climate warming than the more diverse mixed forest catchments.

Ocean warming, a rapid distributional shift, and the hybridization of a coastal fish species - Warren M. Potts; Romina Henriques; Carmen V. Santos; Kate Munnik; Isabelle Ansorge; Francois Dufois; Anthony J. Booth; Carola Kirchner; Warwick H.H. Sauer; Paul W. Shaw (Global Change Biology, 2014)
Despite increasing awareness of large‐scale climate‐driven distribution shifts in the marine environment, no study has linked rapid ocean warming to a shift in distribution and consequent hybridization of a marine fish species. This study describes rapid warming (0.8 °C per decade) in the coastal waters of the Angola‐Benguela Frontal Zone over the last three decades and a concomitant shift by a temperature sensitive coastal fish species ( Argyrosomus coronus ) southward from Angola into Namibia. In this context, rapid shifts in distribution across Economic Exclusive Zones will complicate the management of fishes, particularly when there is a lack of congruence in the fisheries policy between nations. Evidence for recent hybridization between A. coronus and a congener, A. inodorus , indicate that the rapid shift in distribution of A. coronus has placed adults of the two species in contact during their spawning events. Ocean warming may therefore revert established species isolation mechanisms and alter the evolutionary history of fishes. While the consequences of the hybridization on the production of the resource remain unclear, this will most likely introduce additional layers of complexity to their management.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

A Method for Spatially Explicit Representation of Sub-watershed Sediment Yield, Southern California, USA - Derek B. Booth; Glen Leverich; Peter W. Downs; Scott Dusterhoff; Sebastian Araya (Environmental Management, 2014)

Drought as a Trigger for Rapid State Shifts in Kettle Ecosystems: Implications for Ecosystem Responses to Climate Change - Alex W. Ireland; Robert K. Booth; Sara C. Hotchkiss; Jennifer E. Schmitz (Wetlands, 2012)

Differences in transcriptional patterns of extracellular matrix, inflammatory, and myogenic regulatory genes in myofibroblasts, fibroblasts, and muscle precursor cells isolated from old male rat skeletal muscle using a novel cell isolation procedure - Kevin A. Zwetsloot; Anders Nedergaard; Leigh T. Gilpin; Thomas E. Childs; Frank W. Booth (Biogerontology, 2012)

Population genetic structure and colony breeding system in dampwood termites (Zootermopsis angusticollis and Z. nevadensis nuttingi) - W. Booth; C. S. Brent; D. V. Calleri; R. B. Rosengaus; J. F. A. Traniello; E. L. Vargo (Insectes Sociaux, 2012)

Prevention of K-Ras- and Pten-mediated intravaginal tumors by treatment with camptothecin-loaded PLGA nanoparticles - Jeremy S. Blum; Caroline E. Weller; Carmen J. Booth; Imran A. Babar; Xianping Liang; Frank J. Slack; W. Mark Saltzman (Drug Delivery and Translational Research, 2011)

“You spoil everything!” Indigenous peoples and the consequences of industrial development in British Columbia - Annie L. Booth; Norm W. Skelton (Environment, Development and Sustainability, 2011)

Arctic fisheries catches in Russia, USA, and Canada: baselines for neglected ecosystems - D. Zeller; S. Booth; E. Pakhomov; W. Swartz; D. Pauly (Polar Biology, 2011)

Mixed model association scans of multi-environmental trial data reveal major loci controlling yield and yield related traits in Hordeum vulgare in Mediterranean environments - J. Comadran; J. R. Russell; A. Booth; A. Pswarayi; S. Ceccarelli; S. Grando; A. M. Stanca; N. Pecchioni; T. Akar; A. Al-Yassin; A. Benbelkacem; H. Ouabbou; et al. (Theoretical and Applied Genetics, 2011)

Preparing for climate change in Washington State - Lara C. Whitely Binder; Jennifer Krencicki Barcelos; Derek B. Booth; Meriel Darzen; Marketa McGuire Elsner; Richard Fenske; Thomas F. Graham; Alan F. Hamlet; John Hodges-Howell; J. Elizabeth Jackson; Catherine Karr; Patrick W. Keys; et al. (Climatic Change, 2010)

Precipitation extremes and the impacts of climate change on stormwater infrastructure in Washington State - Eric A. Rosenberg; Patrick W. Keys; Derek B. Booth; David Hartley; Jeff Burkey; Anne C. Steinemann; Dennis P. Lettenmaier (Climatic Change, 2010)

Malaria severity and human nitric oxide synthase type 2 (NOS2) promoter haplotypes - Marc C. Levesque; Maurine R. Hobbs; Charles W. O’Loughlin; Jennifer A. Chancellor; Youwei Chen; Ariana N. Tkachuk; Jennifer Booth; Kistie B. Patch; Sallie Allgood; Ann R. Pole; Carolyn A. Fernandez; Esther D. Mwaikambo; et al. (Human Genetics, 2010)

Potential for phosphonoacetate utilization by marine bacteria in temperate coastal waters - Jack A. Gilbert; Simon Thomas; Natalie A. Cooley; Anna Kulakova; Dawn Field; Tim Booth; John W. McGrath; John P. Quinn; Ian Joint (Environmental Microbiology, 2009)
Summary Phosphonates are organic compounds that contain a C–P bond and are a poorly characterized component of the marine phosphorus cycle. They may represent a potential source of bioavailable phosphorus, particularly in oligotrophic conditions. This study has investigated the distribution of the phnA gene which encodes phosphonoacetate hydrolase, the enzyme that mineralizes phosphonoacetate. Using newly designed degenerate primers targeting the phnA gene we analysed the potential for phosphonoacetate utilization in DNA and cDNA libraries constructed from a phytoplankton bloom in the Western English Channel during July 2006. Total RNA was isolated and reverse transcribed and phosphonoacetate hydrolase ( phnA ) transcripts were PCR amplified from the cDNA with the degenerate primers, cloned and sequenced. Phylogenetic analysis demonstrated considerable diversity with 14 sequence types yielding five unique phnA protein groups. We also identified 28 phnA homologues in a 454‐pyrosequencing metagenomic and metatranscriptomic study from a coastal marine mesocosm, indicating that > 3% of marine bacteria in this study contained phnA . phnA homologues were also present in a metagenomic fosmid library from this experiment. Finally, cultures of four isolates of potential coral pathogens belonging to the Vibrionaceae contained the phnA gene. In the laboratory, these isolates were able to grow with phosphonoacetate as sole P and C source. The fact that the capacity to utilize phosphonoacetate was evident in each of the three coastal environments suggests the potential for widespread utilization of this bioavailable P source.

Epac activation, altered calcium homeostasis and ventricular arrhythmogenesis in the murine heart - Sandeep S. Hothi; Iman S. Gurung; Jennifer C. Heathcote; Yanmin Zhang; Stephen W. Booth; Jeremy N. Skepper; Andrew A. Grace; Christopher L.-H. Huang (Pflügers Archiv - European Journal of Physiology, 2008)

Home range of an estuarine‐dependent fish species Pomadasys commersonnii in a South African estuary - A.‐R. CHILDS; A. J. BOOTH; P. D. COWLEY; W. M. POTTS; T. F. NÆSJE; E. B. THORSTAD; F. ØKLAND (Fisheries Management and Ecology, 2008)
The home range and area use of spotted grunter, Pomadasys commersonnii (Haemulidae) (Lacepède), were investigated in the Great Fish estuary, South Africa. Forty individuals (263–698 mm TL) were surgically implanted with acoustic‐coded transmitters and manually tracked during two periods in 2003. Tagged fish spent on average 68 and 77% of the time in the estuary and the remaining time at sea during the two periods, respectively. While in the estuary, there was large variation in home range size, home range length and the number of home range areas amongst individuals. Larger fish had larger home ranges and more core areas than smaller fish. The home ranges of 29 individuals (74%) occurred in the lower reaches of the estuary, suggesting that the proclamation of a no‐take zone in this high use area could benefit this over‐exploited estuarine fishery species.

Hydroelectricity and fish: a synopsis of comprehensive studies of upstream and downstream passage of anadromous wild Atlantic salmon, Salmo salar, on the Exploits River, Canada - D. A. Scruton; C. J. Pennell; C. E. Bourgeois; R. F. Goosney; L. King; R. K. Booth; W. Eddy; T. R. Porter; L. M. N. Ollerhead; K. D. Clarke (Hydrobiologia, 2008)

Reduced physical activity and risk of chronic disease: the biology behind the consequences - Frank W. Booth; Matthew J. Laye; Simon J. Lees; R. Scott Rector; John P. Thyfault (European Journal of Applied Physiology, 2008)

First detection and confirmation of spring viraemia of carp virus in common carp, Cyprinus carpio L., from Hamilton Harbour, Lake Ontario, Canada - K A Garver; A G Dwilow; J Richard; T F Booth; D R Beniac; B W Souter (Journal of Fish Diseases, 2007)
In June 2006, 150 wild common carp were sampled from Hamilton Harbour, Lake Ontario, Canada. Tissue pools consisting of kidney, spleen and encephalon were screened for viruses as a condition facilitating the export of live carp to France. Cytopathic effect (CPE), indicative of a viral infection, became evident after 8 days of incubation at 15 °C. Eighteen of 30 tissue pools (five fish per pool) eventually demonstrated viral CPE. The viral pathogen was initially cultured and isolated on the epithelioma papulosum cyprini cell line and subsequently shown to produce CPE in the fathead minnow and bluegill fin cell lines. Electron microscopy demonstrated the virus to be a rhabdovirus. Reverse transcriptase‐polymerase chain reaction assay and nucleotide sequence analysis identified the isolate as spring viraemia of carp virus (SVCV). Phylogenetic analysis of a 533 bp region of the glycoprotein gene grouped the Canadian isolate in SVCV genogroup Ia together with isolates from Asia and the USA. Sequence comparisons revealed the Hamilton Harbour, Lake Ontario isolate to be most similar to an isolate obtained from common carp in the Calumet Sag Channel in Illinois in 2003 (98.9% nucleotide identity). This is the first report of the detection of SVCV in Canada.

Spatial patterns in the biology of the chokka squid, Loligo reynaudii on the Agulhas Bank, South Africa - L. J. H. Olyott; W. H. H. Sauer; A. J. Booth (Reviews in Fish Biology and Fisheries, 2007)

The effects of buprenorphine on fentanyl withdrawal in rats - Adrie W. Bruijnzeel; Catherine Marcinkiewcz; Shani Isaac; Matthew M. Booth; Donn M. Dennis; Mark S. Gold (Psychopharmacology, 2007)

Bio‐optical consequences of viral infection of phytoplankton: I. Experiments with the cyanobacterium, Synechococcus sp. - W. M. Balch; J. M. Vaughn; J. I. Goes; J. F. Novotny; D. T. Drapeau; E. S. Booth; C. L. Vining (Limnology and Oceanography, 2007)
Four strains of the cyanobacteria, Synechococcus , were infected with viruses isolated and purified from coastal waters of the Gulf of Maine. Changes in host and virus concentration were observed in time course experiments, along with associated variability in inherent optical properties. There were strong optical shifts before and after lysis in inherent optical properties on time scales commensurate with the viral infection process. Specifically, both backscattering and absorption (particularly in visible wavelengths) increased slightly after infection, but decreased markedly after lysis. The most rapid optical change was seen in in vivo chlorophyll fluorescence, with a slight increase within 2 d after initial infection. Such changes likely reflect fundamental changes in host photophysiology after infection. After host lysis, there was a major drop in bulk Chl a fluorescence, synchronous with a major increase in the ratio of free viruses per host cell. The net effect of the changes in fluorescence and host concentration was an increase in the fluorescence per cell. These optical changes were accompanied by major changes in the submicron particle size spectra as cells were lysed, releasing their intracellular contents.

Vertical distribution and diurnal migration patterns of Jasus edwardsii phyllosomas off the east coast of the North Island, New Zealand - Russell W. Bradford; Barry D. Bruce; Stephen M. Chiswell; John D. Booth; Andrew Jeffs; Simon Wotherspoon (New Zealand Journal of Marine and Freshwater Research, 2005)
The rock lobster Jasus edwardsii forms the basis of important fisheries in south‐eastern Australia and New Zealand. Their long pelagic larval phyllosoma phase (12–24 months) raises many questions as to how the larvae are retained and/or recruited into local populations. Recent attempts to model the dispersal of J. edwardsii phyllosoma have had mixed success at reconstructing settlement patterns. However, these models have either ignored vertical distribution or have used that of the western rock lobster, Panulirus cygnus. We report on the vertical distribution and migration of J. edwardsii phyllosomas, collected in March/April 2003 from the Wairarapa Eddy off the east coast of the North Island, New Zealand, and provide a model to describe their vertical distribution. J. edwardsii phyllosoma were primarily recorded within the upper 100 m over similar depth ranges to those reported for other palinurid and scyllarid species. Well‐defined changes in diel vertical distribution were restricted to late‐stage larvae. Mid‐stage phyllosomas were concentrated in the upper 20 m both day and night. Late‐stage phyllosomas were concentrated in the upper 20 m during the night, but they were absent from the upper 20 m during the day and distributed primarily between 20 and 100 m. Future modelling will benefit from using larval distribution and behaviour patterns specific to J. edwardsii.

Review - John D. Booth; W. Richard Webber; Hideo Sekiguchi; Emmanuel Coutures (New Zealand Journal of Marine and Freshwater Research, 2005)
Scyllarid lobsters, together with the palinurids, have a long‐lived, planktonic phyllosoma larval phase in their early life history followed by a much briefer postlarval phase which at settlement completes the planktonic period of their life cycle. Information on scyllarid larval biology and recruitment mechanisms is fragmentary. Scyllarid species exhibit a wide range of larval recruitment strategies and durations, from entire larval and postlarval phases being completed in just a few weeks within lagoons, through to species that become widely dispersed in ocean basins over many months. In contrast, the phyllosomas of all palinurids so far investigated invariably, over many months, become widely dispersed in the open ocean well beyond the continental shelf. Among scyllarid species a general relationship is apparent between adult size and the extent of larval dispersal. During the planktonic period currents, in combination with larval vertical migratory behaviour, probably play an important role in larval dispersal and return. Although varying greatly in size, the postlarval nisto of most scyllarids appears to be similar in behaviour to the puerulus of palinurids. Nistos are usually (if not always) non‐feeding and appear to alternate between swimming at night and resting on the bottom during the day as they move inshore to regain adult grounds before settling and metamorphosing to the first juvenile lobster instar. Those scyllarids with a somewhat abbreviated larval duration and mainly coastal larval distribution—the “flat” species of Ibacus and Thenus —appear to have succeeded in exploiting local currents and biotic systems to restrict larval dispersal and maintain their place. Based on the characteristics of the larvae and their recruitment mechanisms, there is support for the present division of the Scyllaridae into its four subfamilies, but also backing for revision, particularly of the Ibacinae.

Development of the red rock lobster, Jasus edwardsii, from egg to juvenile - Jiro Kittaka; Katsuyuki Ono; John D. Booth; W. Richard Webber (New Zealand Journal of Marine and Freshwater Research, 2005)
Mature red rock lobster, Jasus edwardsii were air freighted from the North Island, New Zealand to Japan in 1985. During most years since, egg extrusion has taken place during November and December and egg hatching from February to April. In the main experiment, phyllosomas were cultured in 100‐litre containers. Each container had an upwelling system, connected either to a Nanno‐chloropsis culture tank (Experiment 1) or to a coral sand filter tank (Experiment 2). Artemia nauplii and mussel gonad were the main foods provided. The numbers of 1st, 5th, and 15th instars were 12 000, 1500, and 137 respectively in Experiment 1, and 1500, 99, and 67 in Experiment 2. The intervals between Instars 1–4 and 4–14 were 43 and 175 days respectively for Experiment 1, and 43 and 169 days for Experiment 2. In Experiment 1, nine phyllosomas (13–15th instar) died during metamorphosis to the puerulus and a single 17th instar metamorphosed 303 days after hatching, 19 days later moulting into the juvenile. In Experiment 2, six 17th instar larvae metamorphosed 293 days and more after hatching, with all dying over the following 3 days. In an ancillary experiment, 30 phyllosomas were cultured in each of two 30‐litre tanks containing microalgae: survival was higher, 20% and 43% reaching Instars 14/15 and six metamorphosing after 212–274 days. In all experiments, the developmental sequence was generally consistent with that for larvae from the field. Gill buds appeared at the 13th instar and gills were complete at the 17th instar. Improved culture methods are required to reduce late‐stage mortalities.

Patterns of polymorphism detected in the chloroplast and nuclear genomes of barley landraces sampled from Syria and Jordan - J. R. Russell; A. Booth; J. D. Fuller; M. Baum; S. Ceccarelli; S. Grando; W. Powell (Theoretical and Applied Genetics, 2003)

Use of telemetry and hydraulic modeling to evaluate and improve fish guidance efficiency at a louver and bypass system for downstream-migrating Atlantic salmon (Salmo salar) smolts and kelts - D.A. Scruton; R.S. McKinley; N. Kouwen; W. Eddy; R.K. Booth (Hydrobiologia, 2002)

Wavelength-Resolved 3-Dimensional Fluorescence Lifetime Imaging - S. E. D. Webb; S. Lévêque-Fort; D. S. Elson; J. Siegel; T. Watson; M. J. Lever; M. Booth; R. Juskaitis; M. A. A. Neil; L. O. Sucharov; T. Wilson; P. M. W. French (Journal of Fluorescence, 2002)

Larval stages, developmental ecology, and distribution of Scyllarus sp. Z (probably Scyllarus aoteanus Powell, 1949) (Decapoda: Scyllaridae) - W. Richard Webber; John D. Booth (New Zealand Journal of Marine and Freshwater Research, 2001)
Phyllosomata and nistos of Scyllarus sp. Z taken from plankton around and offshore northern New Zealand and in the Tasman Sea are presumed to be those of S. aoteanus Powell, 1949, the most common Scyllarus species in this area. The full larval and postlarval development of this species are described. Three features are characteristic of Scyllarus sp. Z phyllosomata; a dorsal crest on the cephalic shield, dorsal thoracic spines, and a forked telson in middle stages persisting as two prominent spines outreaching the telson posterior margin in the final stage. Scyllarus sp. Z's closest affinities are with a group of Scyllarus species whose phyllosomata have forked telsons in middle stages and medium to strong posterolateral telson spines in the final stage. The nisto is low in profile but distinctive in its armature. Too few Scyllarus sp. nistos have been described to suggest any group to which that of Scyllarus sp. Z can be assigned. The spatial and temporal distribution of the larvae and postlarvae of Scyllarus sp. Z are also described. Although early larval stages and postlarvae are found close to New Zealand, mid‐ and late‐stage larvae are widely distributed, some well beyond the known latitudinal range of the adults. There is probably an extended egg‐bearing and hatching period as early stage larvae are caught in most months. Variable rates of development of the larvae and/or delayed metamorphosis, are also possible.

Effects of solvent on DNA adduct formation in skin and lung of CD1 mice exposed cutaneously to benzo(a)pyrene - Ewan D. Booth; Robert W. Loose; William P. Watson (Archives of Toxicology, 1999)

Studies on the dermal and systemic bioavailability of polycyclic aromatic compounds in high viscosity oil products - David Potter; Ewan D. Booth; Henk C. A. Brandt; Robert W. Loose; Robert A. J. Priston; Alan S. Wright; William P. Watson (Archives of Toxicology, 1999)

Polymorphic chloroplast simple sequence repeat primers for systematic and population studies in the genus Hordeum - J. PROVAN; J. R. RUSSELL; A. BOOTH; W. POWELL (Molecular Ecology, 1999)
In this study we report the development of primers to amplify polymorphic chloroplast simple sequence repeats in the genus Hordeum , which includes cultivated barley ( H. vulgare ssp. vulgare ) and its wild progenitor H. vulgare ssp. spontaneum . Polymorphic products were amplified in a wide range of Hordeum spp. and intraspecific variation was detected in both cultivated and wild barley. A decrease in cytoplasmic diversity was observed between sspp. spontaneum and vulgare as well as between ssp. vulgare landraces and cultivars, which is characteristic of domestication processes in many crop species. We also observed possible evidence for reticulate evolution of H. brachyantherum polyploids, with apparent multiple cytoplasmic introgressions during successive polyploidization events.

Genetic variation of Calycophyllum spruceanum in the Peruvian Amazon Basin, revealed by amplified fragment length polymorphism (AFLP) analysis - J. R. RUSSELL; J. C. WEBER; A. BOOTH; W. POWELL; C. SOTELO‐MONTES† and I. K. DAWSON (Molecular Ecology, 1999)
An understanding of the level, structure and origin of genetic variation within and among populations of tropical trees is essential for devising optimum management strategies for their sustainable utilization and conservation. Here, amplified fragment length polymorphism (AFLP) analysis was used to partition genetic variation within and among nine populations of the predominantly riverine tree, Calycophyllum spruceanum , sampled across a wide geographical range along river tributaries of the Peruvian Amazon Basin. Analysis of molecular variance ( AMOVA ) employed 65 AFLP markers and revealed most variation among individuals within populations (91%), although variation among populations was highly significant ( P AMOVA indicated a degree of structuring among populations based on geographical proximity, although clustering did not depend on geographical distance alone. No firm evidence was obtained for unidirectional seed dispersal by water playing an important role in determining genetic structure over the geographical range sampled. Implications of data for optimising genetic management of the species are discussed and areas for further study identified.

Activation of the skeletal α-actin promoter during muscle regeneration - Daniel R. Marsh; James A. Carson; Lynn N. Stewart; Frank W. Booth (Journal of Muscle Research and Cell Motility, 1998)

Correlation of 32 P-postlabelling-detection of DNA adducts in mouse skin in vivo with the polycyclic aromatic compound content and mutagenicity in Salmonella typhimurium of a range of oil products - Ewan D. Booth; Henk C. A. Brandt; Robert W. Loose; William P. Watson (Archives of Toxicology, 1998)

Remote monitoring of heart rate as a measure of recovery in angled Atlantic salmon, Salmo salar (L.) - W. G. Anderson; R. Booth; T. A. Beddow; R. S. McKinley; B. Finstad; F. Økland; D. Scruton (Hydrobiologia, 1998)

Myogenin mRNA is elevated during rapid, slow, and maintenance phases of stretch-induced hypertrophy in chicken slow-tonic muscle - James A. Carson; F. W. Booth (Pflügers Archiv - European Journal of Physiology, 1998)

Introgression of quantitative trait loci (QTLs) determining stripe rust resistance in barley: an example of marker-assisted line development - T. Toojinda; E. Baird; A. Booth; L. Broers; P. Hayes; W. Powell; W. Thomas; H. Vivar; G. Young (Theoretical and Applied Genetics, 1998)

Molecular and biological characterization of new strains of murine cytomegalovirus isolated from wild mice - T. W. M. Booth; A. A. Scalzo; C. Carrello; P. A. Lyons; Helen E. Farrell; G. R. Singleton; G. R. Shellam (Archives of Virology, 1993)

Determination of genotoxic polycyclic aromatic hydrocarbons in a sediment from the Black River (Ohio) - W. Raymond West; Philip A. Smith; Gary M. Booth; Stephen A. Wise; Milton L. Lee (Archives of Environmental Contamination and Toxicology, 1986)

Effects of dietary endrin on reproduction of mallard ducks (Anas platyrhynchos) - Kyle J. Roylance; Clive D. Jorgensen; Gary M. Booth; Melvin W. Carter (Archives of Environmental Contamination and Toxicology, 1985)

An agro-economic assessment of seed-potato storage technologies in the Philippines - Michael J. Potts; W. V. D. Albert; Felix R. Rutab; Elmo O. Sano; Pepito P. Mariano; Robert H. Booth (American Journal of Potato Research, 1983)